The role of Personal Development Planning (PDP) for employer sponsored students - an exploration of how PDP learning activities can support CPD and workforce development requirements - Julie Savory (Association for Learning Development in Higher Education (ALDinHE), 2010)
Over the past decade government policy has emphasised the need for effective and active partnerships between employers and higher education providers (DfES, 2003; Wedgewood, 2007; CBI, 2008; BIS, 2009) to meet the requirements of a globalised knowledge economy. This paper discusses the findings from a research project undertaken at the University of Salford which sought to explore how: • Personal Development Planning (PDP) input can support the development of employability skills for part-time sponsored students. • Employer engagement could be drawn upon to enhance such provision.